Analisis Yuridis Tindak Pidana Penipuan; Studi Kasus Berdasarkan Berita Acara Pemeriksaan (No. Pol: Lpb/177/X/2025/SPKT/Polres Lembata /Polda NTT) - Samara, Finsensius; Balo, Sheva Miha; Opat, Gresila Septuaginta; Seran, Maria Wilfrida Raimunda; Malairu, Madeleina Adira De; Lena, Ignasius Sprianus (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the crime of fraud as stipulated in Articel 378 of the criminal code (KUHP) through a legal analysis of the investigation Report (BAP) in a case involving fraudulent promises of passing civil servant candidates (CPNS) at the ministry of Low and Human Rights. The research focuses on assessing the completeness and strength of the BAP in proving the fulfillment of the elements of the crime of fraud. the research method used is normative legal research with a case approach, utilizing primary data in the from of the BAP from the examination of victim witnessess and secondary data in the from of relevant laws and legal literature. The results indicate that the BAP contains a chronological description of events, consistent testimony from victim witnessess, and sufficient evidence to prove the fraudulent act, the transfer of money by the victim, a causal relationship, and teh intent to unlawfully benefit oneself. therefore, all elements of the crime of fraud as stipulated in article 378 of the criminal code are met, and the case is legally worthy of proceeding to prosecution and trial. This researarch is expected to contribute to improving the quality of police investigation reports (BAP) and the accuracy of evidence in hadling fraud cases.